Diabetes Is the Most Critical Risk Factor of Adverse Complications After Peritoneal Dialysis Catheter Placement - Chang, Hsiao-Huang; Chang, Ching-Hsiang; Hsiao, Chen-Yuan; Kao, Shih-Yi; Chen, Jinn-Yang; Chen, Tien-Hua; Tsai, Pei-Jiun (Frontiers in Medicine, 2021)
Introduction: Peritoneal dialysis (PD) is a kind of renal replacement therapy for end-stage-renal-disease (ESRD). While PD has many advantages, various complications may arise. Methods: This retrospective study analyzed the complications of ESRD patients who received PD catheter implantation in a single medical center within 15 years. Results: This study collected 707 patients. In the first 14 days after PD implantation, 54 patients experienced bleeding complications, while 47 patients experienced wound infection. Among all complications, catheter-related infections were the most common complication 14 days after PD implantation (incidence: 38.8%). 323 patients experienced PD catheter removal, of which 162 patients were due to infection while 96 were intentional due to kidney transplantation. Excluding those whose catheters were removed due to transplantation, the median survival of the PD catheter was 4.1 years; among them, patients without diabetes (DM) were 7.4 years and patients with DM were 2.5 years (p<0.001). Further, 50% probability of surviving was beyond 3.5 years in DM patients with HbA1C＜7 and 1.6 years in DM patients with HbA1C≧7 (p<0.001). Conclusions: Catheter-related infections were the most common complications following PD catheter implantation. DM, especially with HbA1C≧7, significantly impacted on the catheter-related infection and the survival probability of the PD catheter.